PERHITUNGAN BOBOT RESIKO KREDIT DENGAN PENDEKATAN ADVANCED INTERNAL RATING BASED (AIRB) MODEL LGD - Arina Hidayati, Nur (Jurnal Ilmiah AdMathEdu, 2011)
The Calculation of minimum capital charges with LGD model of AIRB approach is one of ways to calculate the credit risk weight, a part of banks efforts in managing the risks occurred because of defaulted debtors. In the AIRB approach, it is required components risks required to calculate the minimum capital charges, namely Probability of Default (PD), Loss Given Default (LGD),   Maturity (M). In addition, this model is also needed other risk components, namely: Conditional Probability of Default (CPD), Conditional Loss Given Default (CLGD) and Maturity Adjustment (MatAd). CLGD is a form of LGD modeling where the CLGD formulation formed by using beta distribution.